ChanceMINT. NRW - Studienbiografische Wendepunkte und Karriereperspektiven - Auferkorte-Michaelis, Nicole
The ChanceMINT. NRW project provides insights into professional practice, prepares students for their career entry and motivates them to shape the course of their studies with self-confidence. Together with partners from industry, committed female students visit major construction sites, sewage treatment plants and planning offices and talk to experts from partner companies about hurdles, successes and professional challenges
2.3.1 Ergebnisqualität im Programm ChanceMINT. NRW: Zieldefinitionen
Keywords: Femmes en informatique; Femmes en ingénierie; Ingénierie; Adult education, continuous learning; Computer science; Education / Adult & Continuing Education; Engineering; Women in computer science; Women in engineering; Computer science -- Vocational guidance -- Germany -- North Rhine-Westphalia; Engineering -- Vocational guidance -- Germany -- North Rhine-Westphalia; Women in computer science -- Germany -- North Rhine-Westphalia; Women in engineering -- Germany -- North Rhine-Westphalia; Ingenieurstudium; Informatikstudium; Frauenförderung; Nordrhein-Westfalen; actors in the promotion of women; Akteur*innen der Frauenförderung; gender mainstreaming and diversity management; Gender Mainstreaming und Diversity- Management; Hochschulen mit MINT-Akteursgruppen; Lehr- und Studienqualitätsentwickler*innen; teaching and study quality developers; Universities with MINT actor groups; Germany / North Rhine-Westphalia; Electronic books